Systematic review: Outcomes of bariatric surgery in patients with inflammatory bowel disease and de-novo IBD development after bariatric surgery. Issue 2 (April 2023) - Mian, Areeb; Khan, Shujhat
Abstract: A large proportion of patients diagnosed with inflammatory bowel disease are obese. Outcomes of bariatric surgery in patients with IBD and on IBD disease course itself is not clear. Furthermore, there is some evidence that bariatric surgery can precipitate the development of de-novo IBD. Thus, the aim of this systematic review was to summarise the evidence from the literature surrounding these questions. A comprehensive literature review was conducted based on the preferred reporting items for systematic reviews and meta-analysis guidelines (PRISMA). PUBMED, and MEDLINE databases was searched using a combination of keywords and MeSH terms including "gastric bypass", "sleeve gastrectomy", "Roux-en-Y", "Duodenal switch", "RYGB", "bariatric surgery" and "inflammatory bowel disease", "Crohn's disease", "Ulcerative colitis". Studies published up to March 2020 were included in this analysis. 22 studies met the inclusion criteria. Studies revealed that bariatric surgery is safe and effective for patients with IBD and resulted in significant weight loss at both the 6-month and 12-month time points. Furthermore, multiple studies reported de-novo IBD development following bariatric surgery in a selection of patients. Highlights: - Bariatric surgery is effective for weight-loss in IBD patients - There is an increased rate of surgical complications in IBD patients following bariatric surgery - There is an increased time of hospital stay in IBD patients after bariatric surgery - There is a strong association between the development of de novo Crohn's disease post bariatric surgery